Structural Emigration: The Revival of Portuguese Outflows - Marques, José Carlos (2016)
During the last two centuries, Portugal has witnessed continuous migration flows. Using data from different sources (both from the destination countries and from Portugal), we will show that over the past 30 years Portugal never stopped being a country of emigration and that, in recent times, these outflows have become more diversified in terms both of destination countries and the profiles of the emigrants. Without neglecting emigration flows before 2008, particular attention will be given to emigration flows that developed after the start of the economic crisis. We will show that current Portuguese emigration is not exclusively due to the economic crisis, but also due to the structural characteristics of migration flows, linked to migration networks from the past and the dependence on different migration systems. In the second part, we will reflect on both the relation of the Portuguese state to its emigrant communities, and the current political debates on the recent increase in emigration flows, and their connection to the economic crisis.